2009
DOI: 10.1111/j.1399-302x.2009.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Candida infection and colonization in solid organ transplant recipients

Abstract: Introduction Oral Candida carriage and infection have been reported to be associated with a greater risk for systemic infection in transplant recipients; however, a systematic analysis of the oral Candida titers and species has not been previously conducted. The objectives of this study were to determine the prevalence of oropharyngeal candidiasis, the oral carrier status, Candida titers and species in this population. Methods Ninety kidney and heart transplant subjects and 72 age-matched healthy controls we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 42 publications
4
37
1
2
Order By: Relevance
“…A global analysis using 454 pyrosequencing showed a significant shift in the oral mycobiome, with Epicoccum and Alternaria abundantly colonizing HIV-infected patients but not healthy individuals, whereas Candida was abundant in both groups [16]. In pharmacologically immunosuppressed solid organ transplant recipients both culture and pyrosequencing studies showed the oral mycobiota to be dominated by Candida species [23–25]. Candida species load and diversity were positively correlated with the dose of mycophenolate mofetil in a renal transplant population, suggesting a causal link [24].…”
Section: Influence Of Host Environment On the Oral Mycobiotamentioning
confidence: 99%
“…A global analysis using 454 pyrosequencing showed a significant shift in the oral mycobiome, with Epicoccum and Alternaria abundantly colonizing HIV-infected patients but not healthy individuals, whereas Candida was abundant in both groups [16]. In pharmacologically immunosuppressed solid organ transplant recipients both culture and pyrosequencing studies showed the oral mycobiota to be dominated by Candida species [23–25]. Candida species load and diversity were positively correlated with the dose of mycophenolate mofetil in a renal transplant population, suggesting a causal link [24].…”
Section: Influence Of Host Environment On the Oral Mycobiotamentioning
confidence: 99%
“…C. glabrata has been reported to be the second etiologic agent, after C. albicans , of superficial and invasive candidiasis in adults in the United States [18, 19], whereas, in Europe and Latin America, C. parapsilosis is the specie responsible for approximately 45% of all cases of candidemia [14, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Candida species can trigger infections of the bloodstream and esophagus as well as other organs in RTPs (6,7). Oral candidiasis (OC) can predispose such patients to esophageal candidiasis, an invasive form of infection with significant morbidity (5,8). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that RTPs have considerably higher prevalence of OC than healthy controls (HCs), and this condition is the most frequent oral infection in RTPs, with a prevalence ranging between 7.7% and 46.7% (8-13). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation